On-site Sample Preparation and Introduction to Ion Mobility Spectrometry - Wu, Jie (University of Waterloo, 2009)
Solid phase microextraction (SPME), needle trap device (NTD), and membrane extraction with a sorbent interface (MESI) are solvent-free sample preparation techniques that were developed to perform the rapid routine analysis of organic compounds (VOCs) in various environmental matrices by integrating sampling, extraction, preconcentration and sample introduction procedures into one step. A portable ion mobility spectrometry (IMS) analyzer has some advantages, such as small size, light weight, operability under ambient pressure, air as carrier gas, and sensitivity, all of which make IMS suitable for on-site monitoring for low concentration of analytes. The aforementioned sampling and preconcentration techniques were coupled with a portable IMS analyzer, as well as a thermal desorption unit that can accommodate SPME, NTD and MESI, which was modified and combined with IMS for on-site monitoring of volatile organic compounds (VOCs) from human breath and plant emissions. Experimental results demonstrated that low detection limits were achievable for gaseous analytes, (25 ng/L for acetone (SPME-IMS), 43 ng/mL (NTD-IMS) and 2.3 ng/mL (MESI-IMS) for α-pinene). These three analytical systems were applied for on-site rapid determination of acetone in human breath and α-pinene from plant emissions respectively. The salient features of these systems that make them suitable for on-site monitoring of volatile organic compounds in different sources are: small size, simple operation, fast and/or on-line sampling, rapid analysis.
Keywords: Solid phase microextraction; Needle trap device; Membrane extraction with a sorbent interface; Ion mobility spectrometry; On-site analysis; Volatile organic compound; Chemistry